A Study of Diction in the Indonesian Translation Binatangisme from George Orwell`s Animal Farm - Maya Nur Lindasari (LPPM Universitas Bumigora Mataram, 2021)
This article examined the Indonesian translation of the novel Animal Farm by George Orwell (1945). It was translated into Binatangisme by Mahbub Djunaidi, published in 1983. The diction of the novel was highlighted because diction was one of the important elements in the acceptability and accuracy words in literary works that need to be considered. There are three categories of dictions which analyzed in this article such as translation of pronoun, translation of cultural adaptation, and translation of terms and sentencing as proposed by Newmark (1988) and Nida (1964). The qualitative method in the form of content analysis was applied to obtain information data that are objective, systematic, and descriptive quantitative about what appears in the choice of diction. The data were collected through close reading which highlighting or giving comments in the forms of monologues and dialogues as well as phrases and sentences. While the data analysis was compared between the source language and the target language. As the result, the translation was near to the target language culture. Mostly, the translator tend to describe the meaning through detailed explanation and used more specific meaning words.